Comparative study of Methotrexate and Cyclosporine in the treatment of Psoriasis - D Karn; A Amatya; R Khatri (Nepal Journal of Dermatology, Venereology & Leprology)
Background Psoriasis is a chronic skin disease characterized by sharply demarcated, erythematous squamous lesions, with an estimated worldwide prevalence of 0 to 11.8%. Methotrexate (MTX) and cyclosporine (CsA) are well known systemic therapies for moderate to severe chronic plague psoriasis.